Improving Students’ Learning Activities and News Listening Competence Throug The Implementation of Method Drilling Using Media Audio Visual In Junior High School Ummi A’yuni Perbaungan - Muhammad Fandy, Fajar; Sutikno (PT Inovasi Pratama Internasional, 2025)
The objectives of this research are (1) to determine the increase in learning activities while listening to news by applying the drill method using audio-visual media in class VII students of Ummi A'yuni Perbaungan IT Private Middle School for the 2024-2025 Academic Year; and (2) to determine the increase in skills listening to the news by applying the practice method (driil) using audio-visual media for class VII students of Ummi A'yuni Perbaungan IT Private Middle School for the 2024-2025 Academic Year. The form of this study was Classroom Action research. The subjects of this research were 25 class VII students of the Ummi A'yuni IT Private Middle School in Perbaungan in the 2024-2025 academic year. Each cycle consisted of three stages: (1) observation, (2) analysis of research results, and (3) reflection. The results of the research show that there is a 60% increase in learning activities and news listening skills in class VII students of Ummi A'yuni Perbaungan IT Private Middle School for the 2024-2025 academic year using the drill method with audio-visual media. The average value in cycle I was 65.2 and in cycle II, the average value was 70.8, indicating an increase of 5.6 or 44%. Furthermore, in cycle III, the average student score increased by 14.5 or 16% compared to the previous results. Changes in the attitudes and behavior of class VII students at Ummi A'yuni Perbaungan IT Private Middle School for the 2024-2025 academic year show positive changes, and students are more interested and enthusiastic about learning to listen to the news. Teacher activities in preparation, presentation, learning methods, and characteristics also showed very good changes